Improving English Reading Comprehension via Murdoch Integrated Approach on Students of Grade 5 in Thailand - Weerawong, Prissana; Chano, Jiraporn; Wu, Chicheng (Naifaderu Cipta Sejahtera, 2025)
Purpose This study aimed to test the effect of the Murdoch Integrated Approach (MIA) on English reading comprehension and analytical reading skills among Thai Grade 5 students. Methodology A one-group pretest-posttest design was employed with 37 Grade 5 students as participants. The intervention consisted of eight 16-hour MIA learning sessions conducted over one semester. Two 30-item multiple-choice tests—one for reading comprehension and one for analytical reading—were administered before and after the intervention. The tests were validated by experts, with Item-Objective Congruence (IOC) values between 0.60 and 1.00. Discrimination indices and reliability coefficients were also reported for both tests. Results/Findings Dependent t-test results showed significant improvements in both reading comprehension and analytical reading scores. Reading comprehension scores increased from 15.08 to 20.78 (t(36) = 9.5, p < .000), and analytical reading scores improved from 14.57 to 18.11 (t(36) = 8.77, p < .000). Implication These findings suggest that the Murdoch Integrated Approach has potential to enhance students' reading skills. However, the absence of a control group means findings should be interpreted with caution. Future research using a true experimental design is recommended to provide stronger evidence of MIA's effectiveness